Clinical significance of platelet-to-white blood cell ratio in patients with Wilson disease: a retrospective cohort study - Hao-Jie Zhong; Jun-Yi Chen; Wei-Ming Wu; Xing-Xiang He; Yong-Qiang Zhan (PeerJ)
Objective To assess the correlation between the platelet-to-white blood cell ratio (PWR) and the severity of liver dysfunction, hepatic complications, and prognosis in Wilson disease (WD) patients. Methods A retrospective analysis was conducted on medical records from January 1, 2016, to March 30, 2022. Both univariate and multivariate analyses were performed to examine the impact of a low PWR (<26.3) on WD severity, liver complications, and disease progression. Additionally, the effect of splenectomy on PWR was evaluated. Results The study included 315 patients with WD, among whom 105 had a low PWR and 210 had a high PWR. Those with low PWR exhibited significantly elevated levels of bilirubin, international normalized ratio, prothrombin time, procollagen type-III N-terminal propeptide, type IV collagen, hyaluronic acid, and portal vein diameter. Conversely, they had lower levels of albumin, total cholesterol, low-density lipoprotein cholesterol, and triglycerides (all P < 0.05). A low PWR correlated with a greater incidence of splenomegaly/hypersplenism, esophagogastric varices, and ascites (all P < 0.05). Furthermore, low PWR independently predicted hepatic decompensation (P < 0.05), and splenectomy led to a marked increase in PWR among WD patients (P < 0.001). Conclusion A low PWR in WD patients is linked to heightened disease severity, increased risk of liver complications, and rapid progression to decompensation. The results imply that splenectomy, by enhancing PWR, may serve as a viable strategy to slow WD progression.